2015
DOI: 10.1007/s10339-015-0740-7
|View full text |Cite
|
Sign up to set email alerts
|

The role of rhythm in perceiving speech in noise: a comparison of percussionists, vocalists and non-musicians

Abstract: The natural rhythms of speech help a listener follow what is being said, especially in noisy conditions. There is increasing evidence for links between rhythm abilities and language skills; however, the role of rhythm-related expertise in perceiving speech in noise is unknown. The present study assesses musical competence (rhythmic and melodic discrimination), speech-in-noise perception and auditory working memory in young adult percussionists, vocalists and non-musicians. Outcomes reveal that better ability t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
92
0
8

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 91 publications
(111 citation statements)
references
References 68 publications
11
92
0
8
Order By: Relevance
“…Musicians have shown advantages in many of the same neural processes that are impaired in individuals with learning and language deficits such as dyslexia and autism, suggesting that music‐based programs may be effective in educational and clinical settings to support the development and remediation of language and listening skills (reviewed in Tierney & Kraus, ). Converging evidence reveals links between rhythm abilities and language skills (Thomson & Goswami, ; Corriveau & Goswami, ; Huss et al ., ; Tierney & Kraus, ; Slater & Kraus, ), suggesting that the transfer of skills from music to speech processing may be mediated in part by enhanced rhythm skills (Shahin, ). Rhythmic expertise therefore provides a particularly interesting context for future research given the potential role of rhythm and timing abilities as markers of language development (Holliman et al ., ; Dellatolas et al ., ; Tierney & Kraus, ; Woodruff Carr et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…Musicians have shown advantages in many of the same neural processes that are impaired in individuals with learning and language deficits such as dyslexia and autism, suggesting that music‐based programs may be effective in educational and clinical settings to support the development and remediation of language and listening skills (reviewed in Tierney & Kraus, ). Converging evidence reveals links between rhythm abilities and language skills (Thomson & Goswami, ; Corriveau & Goswami, ; Huss et al ., ; Tierney & Kraus, ; Slater & Kraus, ), suggesting that the transfer of skills from music to speech processing may be mediated in part by enhanced rhythm skills (Shahin, ). Rhythmic expertise therefore provides a particularly interesting context for future research given the potential role of rhythm and timing abilities as markers of language development (Holliman et al ., ; Dellatolas et al ., ; Tierney & Kraus, ; Woodruff Carr et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have already shown interactions between language function and musicianship, both behaviorally (Slater & Kraus, ) and neurally (Musacchia et al, ). Hence, in light of the present results, it is plausible to suggest that the development of language lateralization and musicianship shares some cerebral factors.…”
Section: Discussionmentioning
confidence: 93%
“…Some of the most overlapping findings between musicians and right‐lateralized persons are: (a) greater gray matter density and volume in the right auditory cortex in musicians (Bermudez, Lerch, Evans, & Zatorre, ; Palomar‐García, Zatorre, Ventura‐Campos, Bueichekú, & Ávila, ) and rightward asymmetry of a portion of the auditory cortex in right‐lateralized persons (Greve et al, ); (b) a higher incidence of duplications in both HG in musicians (Benner et al, ) and a loss of leftward language lateralization when the left HG is duplicated (Tzourio‐Mazoyer et al, ); (c) a higher fractional anisotropy in the right arcuate fasciculus in musicians (Halwani, Loui, Rüber, & Schlaug, ) and a rightward asymmetry of arcuate fasciculus volume in right‐lateralized persons (Sreedharan et al, ); and (d) a thicker cortex in the right pars triangularis in musicians, correlating positively with pitch discrimination ability in nonmusicians (Bermudez et al, ; Novén, Schremm, Nilsson, Horne, & Roll, ), and a rightward asymmetry of Broca's area in right‐lateralized persons (Foundas et al, ; Josse et al, ; Keller et al, ). In fact, language and music are processes whose relationship has been demonstrated through interactions at the subcortical level of processing (Musacchia, Sams, Skoe, & Kraus, ) and the performance of some language skills (Slater & Kraus, ). Thus, given the similarity in the neuroanatomical correlates of the two conditions, we hypothesized that atypical language dominance would be found more frequently in left‐handed musicians than among left‐handed nonmusicians.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the supplementary motor area (SMA), known to be involved in articulation of speech and the preparation of movement, is also engaged when performing music, imagining listening to music or imagining performing to music (Herholz and Zatorre, 2012;, and plays an important role in planning music segment by segment during performanceboth in terms of rhythm and melody sequencing (de Manzanö and Ullén, 2012). The link between the basal ganglia and the SMA along the dorsal route is congruent with the finding that the ability to synchronize with a beat is positively correlated with better pre-reading skills such as segmenting the speech stream and better neural encoding of speech and language (Carr White-Schwoch, Tierney et al, 2014;Slater & Kraus, 2016), better subcortical neural timing in adolescents (Tierney and Kraus, 2013a) as well as better cognitive and linguistic skills (Tierney and Kraus, 2013b).The integration of sensory and motor information may provide a mechanism for predicting sequence timing (Large, Herrera, and Velasco, 2015), such as the processes that ensure the smooth flow in a conversation.…”
Section: The Relationship Between Music and Languagementioning
confidence: 87%